PENGARUH PENGETAHUAN, PENGALAMAN KERJA, KOMPETENSI SDM DAN PENGEMBANGAN KARIER TERHADAP PRESTASI KERJA PERSONEL POLSEK PAMEKASAN - jurnalmap map; Achmad Albunsyary; Muninghar ÔÇì; Fatimah Riswati (MAP (Jurnal Manajemen dan Administrasi Publik), 2020)
ABSTRACT This research was conducted in Pamekasan Police Office with the number of research samples of 42 personnel, The purpose of this study is 1) To know and describe about knowledge, work experience, human resource competence and career development on the work performance, 2) To test and analyze whether knowledge, work experience, HR competence and career development have a simultaneous and significant influence on the work performance, 3) To test and analyze whether the knowledge significantly affect the work performance. The results showed that simultaneously, knowledge, work experience, human resource competence and career development have a significant influence on the work performance. Partially, knowledge, work experience, human resource competence and career development have a significant influence on the work performance, human resource competence and career development have a significant influence on the work performance of pamekasan police personnel. Keywords: Knowledge (X1), Work Experience (X2), Human Resource Competency (X3), and Career Development (X4) and Job Performance (Y)